“是” As An Adverb - Wichaksamethi, Onnarin; Supsiriphan, Wasan (Chophayom Journal, 2023)
This academic paper aims to present the function of “是”in Chinese. In addition it is used as a verb in sentences, which is the “是” in the adverbial function. Theve are some studies the use of “是” in research papers, academic papers, through more than 1,000 example sentences found in the 2023 Center for Chinese Linguistics PKU ( CCL ) archives of Peking University. It was found that “是” used in the adverb form is significantly different from “是”. In other words, “是” as a verb plays a role in linking the relationship between the subject and the object of the sentence. Moreover, it acts acts as a predicate in a sentence. While the adverb “是”doesn't connect the subject and the object in the sentence but it only serves to emphasize the components or express the intonation of that sentence. The “是” functions in this way is often found in sentences after “是” as a verb, phrasal verb, adjective, adjective phrase and the phrase “的”, where “是” is placed before the words or phrases act as an modifier to modify those words or phrases, it isn't the predicate in the sentence. In addition, another feature of “是” that functions as an adverb in the sentence can be omitted and does not affect the meaning of the sentence. From the study of the position of “是” in a sentence. was found that the adverb “是” appears in two forms are “noun + 是 + word or phrase that is not a noun or noun phrase” and “是 + ………..的”. Keyword: 是, Grammatical Role, Adverb